Proper Names as Bearers of National and Cultural Information (Proceedings of Southern Federal University. Philology, 2017)
Veronika V. Katermina (Krasnodar, Russian Federation)The problem of «a person and a language» as well as «a language and a culture» becomes very actual nowadays. It is evident that an adequate research of a language is possible only if you are out of its «reach», if you are aimed at a person – the creator of a language. Moreover, this approach can be achieved on the definite national-cultural material. A proper name is a border which divides existence and non-existence, universal and nationalspecific. It can be even «a point», a place, where they are divided and met. A proper name allows to a certain extent to see a social status, inner world, national peculiarities of both a named and a naming. In this article a part of a research of axiological parameters of life of Russian people is shown. It is based on the Russian connotative proper names. Russian people name the things around the plants, trees, birds and animals by proper names indicating their importance and significance in the life of a person and a society. The variety of naming the objects in different areas is shown by a great number of dialect local meanings of proper names. Being a cultural dominating idea and functioning as a national-cultural component proper names help to determine peculiarities, distinctive features of this or that nation, this or that type of a language personality. In this way, being a vital element, proper names take an important part in the system of any language and culture. With their help one can single out national-cultural peculiarities of a definite people.Key words: proper name, language, culture, national and cultural component, connotation, lexicography.DOI 10.23683/1995-0640-2017-4-166-174  Quote:Katermina, V. V. (2017). Proper Names as Bearers of National and Cultural Information. Proceedings of Southern federal university. Philology. 4, 166‒174.